Odstopanje od minimalnih standardov v kolektivnih pogodbah dejavnosti - Kresal Šoltes, Katarina (Delavci in delodajalci, 2018)
The paper analyses the content of the existing Slovenian collective agreements in the private sector concerning the question whether they contain provisions derogating from the minimum labour law standards and the provisions allowing a derogation of minimum standards agreed by sector collective agreements at lower levels of collective bargaining. The author points out the inappropriate practice of social partners, which can destabilize the collective bargaining system and weaken trade union and employer organisations at the sector and the national level.
Keywords: delovno pravo; kolektivne pogodbe; minimalni standardi; odstopanje; zasebni sektor